Additive manufacturing ferromagnetic polymers using stereolithography – Materials and process development. (August 2019) - Nagarajan, Balakrishnan; Arshad, Muhammad; Ullah, Aman; Mertiny, Pierre; Qureshi, Ahmed Jawad
Abstract: Magnetic field responsive polymer composites find applications in many electrical and electronic devices. In this study, composites with magnetic fillers were manufactured using a stereolithography based AM process. Magnetic suspensions developed with an objective of controlling particle settling were characterized for rheological properties. A stereolithography based commercial 3D printer was utilized to fabricate components using the developed magnetic suspensions. Resulting magnetic composite structures were characterized using scanning electron microscopy, a coordinate measuring machine and Fourier transform infrared spectroscopy. Through this research an enhanced understanding of filler modified polymers development, material behaviour and the process for manufacturing magnetic field responsive composites using stereolithography is obtained.